Impact of Specialty Training on the Association between Flap Size and Incidence of Complications following Microvascular Head and Neck Reconstruction for Cancer - Offodile, Anaeze C., II; Aherrera, Andrew S.; Wenger, Julia; Tsai, Thomas; Orgill, Dennis P.; Guo, Lifei (Journal of Reconstructive Microsurgery, 2015)
Background The scope of otolaryngology and plastic surgery overlap within head and neck reconstruction is increasing; yet comparative outcome studies between these two subspecialties are limited.Methods A retrospective review was performed on all patients who underwent microvascular reconstruction of a postablative head and neck defect at a quaternary academic medical center between January 2000 and October 2011. Postoperative outcomes were reviewed by subspecialty and Mann–Whitney analysis was used to investigate any flap size differences between cohorts with and without complications.Results A consecutive series of 129 (66.8%) otolaryngology cases and 64 (33.2%) plastic surgery cases comprised the entire study sample. Plastic surgery flaps were significantly larger than otolaryngology flaps (9.7 vs. 8.5 cm, p = 0.004). Flap complication rates (31.8 vs. 37.5%, p = 0.429) and flap failure rates (5.4 vs. 4.7%, p = 0.429) were comparable between subspecialties. However, a significant difference in flap size was evident between the cohorts with and without flap complications following microvascular reconstruction by otolaryngology (9.18 vs. 8.15 cm, p = 0.042). This difference was not detected following reconstruction by plastic surgery (9.34 vs. 9.04 cm, p = 0.225). For the overall sample, there was a correlation between increasing flap size and higher tumor stages (significant at T4, p = 0.003) as well as advanced T-stage and medical complications (p = 0.004).Conclusion Plastic surgeons should maintain an active role in the reconstruction of complex, microvascular head and neck cases such as those that require larger flaps and/or of advanced T-stages.
Keywords: head and neck reconstruction; free flap reconstruction; postoperative outcomes